2021
DOI: 10.3390/cancers14010101
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Metastatic Breast Cancer Lesions on 18F-FDG PET/CT Longitudinal Acquisitions for Treatment Response Assessment

Abstract: Metastatic breast cancer patients receive lifelong medication and are regularly monitored for disease progression. The aim of this work was to (1) propose networks to segment breast cancer metastatic lesions on longitudinal whole-body PET/CT and (2) extract imaging biomarkers from the segmentations and evaluate their potential to determine treatment response. Baseline and follow-up PET/CT images of 60 patients from the EPICUREseinmeta study were used to train two deep-learning models to segment breast cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, manual segmentation of all lesions is time consuming in clinical practice, especially in patients with multiple metastases. For this reason, Moreau and colleagues [ 46 ] trained two deep-learning models in order to automatically segment BC metastatic lesions on the baseline and follow-up FDG PET/CT of 60 patients. The authors assessed four imaging biomarkers, i.e., SULpeak, TLG, PET Bone Index, and PET Liver Index, with SULpeak identified as the best biomarker to assess patients’ response (sensitivity 87%, specificity 87%), representing a promising tool for automatic segmentation of metastatc BC lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, manual segmentation of all lesions is time consuming in clinical practice, especially in patients with multiple metastases. For this reason, Moreau and colleagues [ 46 ] trained two deep-learning models in order to automatically segment BC metastatic lesions on the baseline and follow-up FDG PET/CT of 60 patients. The authors assessed four imaging biomarkers, i.e., SULpeak, TLG, PET Bone Index, and PET Liver Index, with SULpeak identified as the best biomarker to assess patients’ response (sensitivity 87%, specificity 87%), representing a promising tool for automatic segmentation of metastatc BC lesions.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the prediction of metastasis at distance at baseline PET imaging was performed by only one paper [ 50 ], but with encouraging results. Similarly, radiomic-assisted therapy response assessment was only explored by one study [ 46 ], which introduced an interesting automatic segmentation of BC lesions using DL. We encourage researchers to investigate the potentialities of radiomic analysis and AI also on these clinical settings of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Even though LFPN achieves a slightly lower F1-score alone than self-training, models with self-training require twice the training time than the semi-supervised approach. Some studies have also suggested pretraining the model with unlabeled data from related datasets to overcome the lack of labeled data [ 45 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apiparakoon et al [ 56 ] augmented a dataset by changing the light, contrast, and brightness to ensure consistency with the physician’s process. Several other augmentation techniques have been employed, including rescaling [ 13 , 33 , 39 , 43 , 44 , 45 , 54 , 58 , 59 , 60 , 98 , 107 ], rotation [ 13 , 33 , 39 , 43 , 44 , 45 , 54 , 58 , 59 , 60 , 77 , 98 , 107 ], zooming [ 13 , 44 , 107 ], shifting intensity [ 58 , 77 ], reflecting horizontally [ 77 ], translating the image [ 39 , 43 , 77 ], cropping [ 59 ], applying elastic deformations [ 45 ], gamma augmentation [ 45 ], and flipping [ 13 , 44 , 54 , 59 , 107 ]. Da Cruz et al [ 60 ] further applied a probabilistic Gaussian blur and linear contrast filters to augment the dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation